Aerobic training and postexercise protein in facioscapulohumeral muscular dystrophy: RCT study. (4th August 2015) - Andersen, Grete; Prahm, Kira P.; Dahlqvist, Julia R.; Citirak, Gülsenay; Vissing, John
Abstract : Objective: To investigate the effect of regular aerobic training and postexercise protein-carbohydrate supplementation in patients with facioscapulohumeral muscular dystrophy (FSHD). Methods: In this randomized, double-blind, placebo-controlled parallel study, we randomized untrained men (n = 21) and women (n = 20) with FSHD (age 19–65 years) to 2 training groups—training with protein supplement (n = 18) and training with placebo supplement (n = 13)—and a nonintervention control group (n = 10). We assessed fitness, walking speed, muscle strength, questionnaires, and daily activity levels before and after 12 weeks of interventions. Training involved 36 sessions of 30-minute cycle-ergometer training. After each session, patients drank either a protein-carbohydrate or placebo beverage. Results: In the trained participants, fitness, workload, and walking speed improved (10% [confidence interval (CI) 4%–15%], 18% [CI 10%–26%], 7% [CI 4%–11%], respectively, p < 0.001, number needed to treat = 2.1). Self-assessed physical capacity and health (Short Form–36) also improved. Muscle strength and daily activity levels did not change with training. Protein-carbohydrate supplementation did not result in further improvements in any tests compared to training alone. Conclusions: This randomized, controlled study showed that regular endurance training improves fitness, walking speed, and self-assessed health in patients with FSHD without causing muscle damage. Postexercise protein-carbohydrate supplementation does not add any further improvement to training effects alone. Classification of evidence: This study provides Class II evidence that regular aerobic training with or without postexercise protein-carbohydrate supplementation improves fitness and workload in patients with FSHD.